Do different kinds of introductions influence comprehension and memory for scientific explanations?. Issue 5 (3rd July 2021) - Mensink, Michael C.; Kendeou, Panayiota; Rapp, David N.
ABSTRACT: Compelling and interesting introductions are considered an important way of fostering reader engagement with expository-text content. But only a handful of projects have examined this prescriptive advice. In three experiments, we examined the effects of two different genres of introductions—narrative and expository—on comprehension and memory for texts providing scientific explanations. In Experiment 1, participants read texts without introductions and subsequently completed either an immediate recall or a delayed recall seven days later for a subset of the texts. In Experiment 2, participants read the same texts including either all narrative or all expository introductions and after reading were asked to complete an immediate recall. In Experiment 3, participants read the same texts, this time half including narrative introductions and half including expository introductions, and completed a delayed recall seven days later for all the texts. Across all experiments, participants recalled more of the scientific explanations when they were preceded by introductions than when they were not, and narrative introductions were better recalled than expository introductions. Participants who read both types of introductions were also slower to read scientific explanations that followed narrative introductions compared to expository. Taken together, these results indicate that introductions influence memory and reading times for scientific explanations but not always in ways that align with popular instructional prescriptions and advice.